(untitled) (Revista Contexto & Educação, 2023)
This article presents an experience of initial teacher training in Early Childhood Education which resulted in discussing training strategies, highlighting the reflective dimensions, based on the Pedagogical Residency Program (PRP) of the Pedagogy course at Universidade Federal de São Paulo (UNIFESP). Based on the pedagogical residency as a reflective thinking laboratory, the article discusses the documentation strategies, based on the online field diary and highlights its potential for the construction of knowledge in the community. It brings subsidies that favor the reflection on the teaching internship in Early Childhood Education, that is on the child, childhood and the way of working pedagogically, transforming experiences into teaching knowledge.